Honour and Shame in the Canadian Muslim Community: Developing Culturally Sensitive Counselling Interventions - Helms, Barbara Lois (Canadian Journal of Counselling and Psychotherapy, 2015)
This article focuses on the issues of honour and shame within the Canadian Muslim community in the context of females who violate collectively held sexual mores. The discussion reviews the body of related research, including multicultural studies on counselling Muslims and research on the specific areas of honour-related violence, domestic abuse, and intergenerational conflict. Relevant concepts from previous studies are drawn together and expanded into a specific intervention model intended as a counselling tool for helping professionals.